2019
DOI: 10.1002/ldr.3347
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term subsidence in Mexico City from 2004 to 2018 revealed by five synthetic aperture radar sensors

Abstract: Anthropogenic land subsidence is an example of changes to the natural environment due to human activities and is one of the key factors in causing land degradation at a range of scales. Previous studies assessing land subsidence in the Valley of Mexico either focused on regional scale or short (noncontinuous) temporal scale. In this study, long‐term land subsidence (~15 years) is mapped in Mexico City (Mexico) using two interferometric synthetic aperture radar (InSAR) methods, namely, GEOS (Geoscience and Eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In the ZMVM, Strozzi and Wegmuller (1999) used 1996 SAR data from the European Remote Sensing (ERS) satellites to isolate 30 cm/year of subsidence. Cabral-Cano et al (2008) and Sentinel-1 data and found similar rates between 2003 and 2016 and Du et al (2019) used multiple sensors to derive an accumulated 2004-2017 subsidence map. Cigna and Tapete (2021) used 2014-2020 Sentinel-1 data and found subsidence rates up to 39 cm/yr.…”
Section: Previous Insar Surveysmentioning
confidence: 91%
“…In the ZMVM, Strozzi and Wegmuller (1999) used 1996 SAR data from the European Remote Sensing (ERS) satellites to isolate 30 cm/year of subsidence. Cabral-Cano et al (2008) and Sentinel-1 data and found similar rates between 2003 and 2016 and Du et al (2019) used multiple sensors to derive an accumulated 2004-2017 subsidence map. Cigna and Tapete (2021) used 2014-2020 Sentinel-1 data and found subsidence rates up to 39 cm/yr.…”
Section: Previous Insar Surveysmentioning
confidence: 91%
“…However, in the past decade subsidence has monitored by advanced satellite geodetic techniques, mainly satellite Interferometric Synthetic Aperture Radar (InSAR) and GPS (e.g. Cabral et al, 2008;López-Quiroz et al, 2009;Osmanoglu et al, 2011;Du et al, 2019). These studies have routinely detected the highest subsidence rates in the eastern sector of the city within two areas that correspond to the former Texcoco and Chalco-Xochimilco lakes (Fig.…”
Section: Land Subsidence In Mexico Citymentioning
confidence: 99%
“…In the past decade, subsidence of the city has been studied with modern geodetic techniques (Cabral-Cano et al 2008;López-Quiroz et al 2009;Osmanoglu et al 2011;Chaussard et al 2014;Du et al 2019;Fernández-Torres et al 2020;Solano-Rojas et al 2020;Cigna and Tapete 2021). In this study, subsidence in CDMX was analyzed using 125 images recorded between November 2014 and October 2017 by the C-band SAR (Synthetic Aperture Radar) instrument onboard the Sentinel 1-A and B in Interferometric Wide Swath, descending mode (Figure 5a).…”
Section: Subsidence Of the Ground In Cdmxmentioning
confidence: 99%